The contribution of Professor Alicja Jaruga to accounting history research - Michał Wiatr (Zeszyty Teoretyczne Rachunkowości)
The purpose of this article is to present prof. Jaruga’s contribution to the development of Polish account-ing history research. It highlights her role as initiator of a number of research projects in this area, ambas-sador of Polish accounting on international arenas, and a person for whom foreign exchange and coopera-tion have always been of primary importance. The article is based on biographical and literature studies